Involvement of the "A" isozyme of methyltransferase II and the 29-kilodalton corrinoid protein in methanogenesis from monomethylamine. - Burke, S A (1995)
An assay which allowed detection of proteins involved in the trimethylamine- or monomethylamine (MMA)-dependent methylation of coenzyme M (CoM) was developed. The two activities could be separated by anion-exchange chromatography. The unresolved activity responsible for MMA:CoM methyl transfer eluted from a gel permeation column in the molecular mass range of 32 kDa. The activity was purified to two monomeric proteins of 40 and 29 kDa. The preparation contained protein-bound corrinoid in a mixture of Co(II) and Co(III) states, as well as methyl-B12:CoM methyltransferase (MT2) activity. N-terminal sequence analysis demonstrated that the polypeptides were two previously identified proteins of undefined physiological function. The smaller polypeptide was the monomeric 29-kDa corrinoid protein. The larger polypeptide was the "A" isozyme of MT2. Individually purified preparations of both proteins increased the rate of MMA-dependent CoM methylation by approximately 1.7 mumol/min/mg of purified protein above background activity in the extract of methanol-grown cells. These results indicate that the 29-kDa corrinoid protein and the "A" isozyme of MT2 function in methanogenesis from MMA. A likely mechanism is that the 29-kDa corrinoid is methylated by MMA and the methyl group is then transferred by the "A" isozyme of MT2 to CoM.